Участь МАРК в опосередкуваннi дiї протипухлинного препарату таксолу на клiтини анапластичного раку щитовидної залози - Попадюк, I.Д.; Пушкарьов, В.М.; Костюченко, Н.М.; Тронько, М.Д. (Видавничий дім "Академперіодика" НАН України, 2008)
The role of MAPK (mitogen-activated protein kinase) in mediating the action of antitumour drug taxol on the cell line of thyroid anaplastic cancer, ARO, is studied. It is shown that taxol enhances the phosphorylation of anti-apoptotic protein Bcl-2 and activated the main executioner caspase-3. Taxol did not activate р38 МАРК but significantly inhibits the activation of ERK1/2, another MAP kinase that participates in survival mechanisms. The possible factor under control of this kinase can be a protein-inhibitor of apoptosis, XIAP. This suggestion is confirmed by experiments with the inhibitor of c-Raf-1/MEK1/ERK cascade, PD98059. In the presence of the inhibitor, the XIAP quantity essentially decreased as well as the cell viability. The possible means of augmentation of the taxol cancerostatic effect upon thyroid cancer cells are discussed.